New perspectives on the treatment of mycobacterial infections using antibiotics - He, Yile; Fan, Aili; Han, Meng; Zhang, Yihan; Tong, Yigang; Zheng, Guojun; Zhu, Shaozhou (Applied microbiology and biotechnology, 2020)
More than 100 years have passed since the discovery of Mycobacterium tuberculosis , in 1882, as the pathogen that causes tuberculosis (TB). However, globally, TB is still one of the leading causes of death by infectious diseases. In 2018, approximately 10.0 million people were diagnosed with TB owing to the development of advanced strategies by M. tuberculosis to resist antibiotics, including the development of a dormant state. The World Health Organization (WHO) and the Sustainable Development Goals (SDGs) are dedicated to ending TB by 2030. However, the development of strategies to discover new TB drugs and new therapies is crucial for the achievement of this goal. Unfortunately, the rapid occurrence of multidrug-resistant strains of M. tuberculosis has worsened the current situation, thereby warranting prioritized discovery of new anti-TB drugs and the development of new treatment regimens in academia and the pharmaceutical industry. In this mini review, we provide a brief overview of the current research and development pipeline for new anti-TB drugs and present our perspective of TB drug innovation. The data presented herein may enable the introduction of more effective medicines and therapeutic regimens into the market. Key Points • The Updated Global New TB Drug Pipelines are briefly summarized. • Novel strategies for the discovery of new TB drugs, including novel sources, bioinformatics, and synthetic biology strategies, are discussed. • New therapeutic options, including living therapeutics and phage therapy, are proposed.